Applied functions of the archive: epistemological, political and educational - Minenko, Andrii (Filosofiya osvity. Philosophy of Education, 2024)
The article explores and formulates the applied functions of the archive. In addition to its function as a resource for understanding the past, the archive has important applied functions in the present. The task of defining the functions of the archive also requires defining the concept of the archive. For this aim, the concept of “archive” in the works of philosophers Alyda Assman, Michel Foucault and Jacques Derrida, as well as Ukrainian researchers – Vitaly Turenko, Volodymyr Prykhodko, Serhii Rudenko, Maryna Palienko, was considered and studied. These philosophers have found a methodological connection with regard to the etymology of the ancient Greek term “Αρχη”. Detailed studies of the semantics of the concept of Αρχη allow to investigate the understanding of the origin of the functions of the archive. The French philosopher Michel Foucault considered the concept of the archive as a component of his ontological system, “Archaeology of Knowledge”, which explains the functioning of human knowledge, memory and power. So, Foucault explained the epistemological function of the archive. Another French philosopher, Jacques Derrida, focuses on the human desire to take hold of the past, which he calls “archive fever,” and develops this concept in his famous work “Archive Fever: A Freudian Impression”. Among the general concepts of the archive, Derrida focuses on the main and important political function of the archive, the embodiment of the archive in the body. The way the archive functioning is an important factor in the political regime, but at the same time it ensures the successful operation of the education system. In its various forms, the archive transmits to posterity information that appears as a warning and instruction based on the experience of the past. Based on these conditions, the archive acquires an important educational function in the modern world and forms the key ideological conditions for the functioning of society.